2002
DOI: 10.1002/clc.4950250105
|View full text |Cite
|
Sign up to set email alerts
|

Trends in long‐term management of survivors of acute myocardial infarction by cardiologists in a government university‐affiliated teaching hospital

Abstract: SummaryBackground: Despite prospective randomized control trials showing that beta blockers, aspirin, angiotensin-converting enzyme (ACE) inhibitors, and lipid-lowering agents improve survival rates after myocardial infarction (MI), these agents are routinely underutilized.Hypothesis: Our aim was to determine the frequency with which cardiologists at a government, university-affiliated teaching hospital prescribe aspirin, beta blockers, ACE inhibitors, calcium-channel blocking agents (CCBs), and lipidlowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Butler's study 23 showed that about 61% of patients still collected their beta-blocker prescriptions 1 year following their MI. But in Mitra's study, 24 of 156 AMI patients discharged from a government Universityaffiliated teaching hospital on beta-blocker treatment 71% patients were still on beta-blocker treatment after 2 years follow-up. The difference in adherence to betablocker treatment between different studies may be explained by different population characteristics, prescribing habits or health care systems or different measurements of adherence.…”
Section: Discussionmentioning
confidence: 95%
“…Butler's study 23 showed that about 61% of patients still collected their beta-blocker prescriptions 1 year following their MI. But in Mitra's study, 24 of 156 AMI patients discharged from a government Universityaffiliated teaching hospital on beta-blocker treatment 71% patients were still on beta-blocker treatment after 2 years follow-up. The difference in adherence to betablocker treatment between different studies may be explained by different population characteristics, prescribing habits or health care systems or different measurements of adherence.…”
Section: Discussionmentioning
confidence: 95%
“…7,9,10,21,22 Yet, in our study population, there is no sign of leveling in the discontinuation rates after 1 year post-AMI. We identified two studies examining adherence beyond the first year post-AMI, 8,11 which have limited generalizability, and more importantly, examine Figure 2. Time to discontinuation for ACEI/ARB therapy patterns from the 1990s, generally focusing on beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…4 Limited data suggest that many patients who initiated these regimes after AMI have low rates of longterm persistence. [7][8][9][10] Beta-blocker or ACEI therapies are indicated for other diseases (e.g., coronary artery disease and hypertension), and studies following patients with such conditions also demonstrated low long-term adherence rates. [10][11][12][13][14][15] To identify subpopulations at greatest risk of therapy discontinuation, this study used administrative data from a large U.S. health plan to describe patient characteristics and comorbidities associated with increased rates of therapy discontinuation during the 2 years after AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Discharge prescriptions and content of these prescriptions are considered as the main criteria of success in patients with acute coronary syndrome [1]. A limited number of data indicate that these prescriptions are written appropriately, but in time patients' compliance with these prescriptions is reduced [2][3][4][5]. After acute MI (myocardial infarction), 24% of the patients do not take all of their medications during the first week of discharge and 1/3 of them leave at least 1 drug in one month [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…) kullanan hastaların oranı % 78.7'di (n=325). İlk yılın sonunda, ASA, statin, beta bloker, anjiyotensin dönüştürücü enzim inhibitörleri / aldosteron reseptör bloker (ADEİ / ARB) ve klopidogrel kullananların oranı sırasıyla; % 88.1'e (n=364), % 66'ya (n=273), % 80.9'a (n = 334),% 69.7'ye (n=288) ve % 81 3…”
unclassified